Rheological Properties of Acrylic Bone Cement Smartset HV - Henrietta Lelovics; Tatiana Liptakova (Communications - Scientific letters of the University of Zilina, 2010)
The rheological behaviour of polymethylmethacrylate bone cement SmartSet® HV prepared by hand and vacuum mixing was characterized using an oscillatory rheometer. Complex viscosity, damping factor, loss and storage modulus were measured by dynamic mechanical thermal analysis (DMTA) after several periods of ageing as a function of temperature for a range of 22–70 °C. Time-dependent changes of measured parameters were observed which were partially influenced by the cement preparation method.